Neuroprotective Effect of the Marine-Derived Compound 11-Dehydrosinulariolide through DJ-1-Related Pathway in In Vitro and In Vivo Models of Parkinson’s Disease - Feng, Chien-Wei (Mar Drugs, 2016)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by tremor, rigidity, bradykinesia, and gait impairment. In a previous study, we found that the marine-derived compound 11-dehydrosinulariolide (11-de) upregulates the Akt/PI3K pathway to protect cells against 6-hydroxydopamine (6-OHDA)-mediated damage. In the present study, SH-SY5Y, zebrafish and rats were used to examine the therapeutic effect of 11-de. The results revealed the mechanism by which 11-de exerts its therapeutic effect: the compound increases cytosolic or mitochondrial DJ-1 expression, and then activates the downstream Akt/PI3K, p-CREB, and Nrf2/HO-1 pathways. Additionally, we found that 11-de could reverse the 6-OHDA-induced downregulation of total swimming distance in a zebrafish model of PD. Using a rat model of PD, we showed that a 6-OHDA-induced increase in the number of turns, and increased time spent by rats on the beam, could be reversed by 11-de treatment. Lastly, we showed that 6-OHDA-induced attenuation in tyrosine hydroxylase (TH), a dopaminergic neuronal marker, in zebrafish and rat models of PD could also be reversed by treatment with 11-de. Moreover, the patterns of DJ-1 expression observed in this study in the zebrafish and rat models of PD corroborated the trend noted in previous in vitro studies.